(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article analyzes the formation of pronominal verbs in the Italian language, studies their role in a sentence and their transformation. The perception of pronominal verbs by Russian speakers is also considered.